2010
DOI: 10.1021/es1031272
|View full text |Cite
|
Sign up to set email alerts
|

Saccharin and Other Artificial Sweeteners in Soils: Estimated Inputs from Agriculture and Households, Degradation, and Leaching to Groundwater

Abstract: Artificial sweeteners are consumed in substantial quantities as sugar substitutes and were previously shown to be ubiquitously present in the aquatic environment. The sweetener saccharin is also registered as additive in piglet feed. Saccharin fed to piglets was largely excreted and, consequently, found in liquid manure at concentrations up to 12 mg/L, where it was stable during 2 months of storage. Saccharin may thus end up in soils in considerable quantities with manure. Furthermore, other studies showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(116 citation statements)
references
References 20 publications
5
107
1
3
Order By: Relevance
“…While for many pharmaceuticals there are multiple sources in the environment globally, it is still possible to elucidate source terms on a local or sub-regional scale (e.g. Clara et al, 2004;Buerge et al, 2009Buerge et al, , 2011. The following sections critically review pollution of groundwater resources by EOCs from key point and diffuse sources.…”
Section: Sources and Pathways For Groundwater Pollution By Eocsmentioning
confidence: 99%
See 2 more Smart Citations
“…While for many pharmaceuticals there are multiple sources in the environment globally, it is still possible to elucidate source terms on a local or sub-regional scale (e.g. Clara et al, 2004;Buerge et al, 2009Buerge et al, , 2011. The following sections critically review pollution of groundwater resources by EOCs from key point and diffuse sources.…”
Section: Sources and Pathways For Groundwater Pollution By Eocsmentioning
confidence: 99%
“…Sarmah et al (2006) reviewed the occurrence and fate of veterinary antibiotics in the environment and reported the occurrence of a range of veterinary antimicrobials at low concentrations in groundwater which were attributed to agricultural practices including the application of manure. Buerge et al (2011) reported the occurrence of saccharin in groundwater at a pumping station in Switzerland, with concentrations up to 260 ng/L, after application of pig manure despite the fact that biological mineralisation in soil was rapid (90% after two months incubation).…”
Section: Diffuse Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pharmaceuticals in groundwater beneath or downgradient of a landfill has been confirmed by several authors [143][144][145][146]. Two recent studies [99,147] investigating the occurrence of groundwater down gradient of landfills detected a range of industrial compounds (detergents, antioxidants, fire retardants, plasticisers) as well as pharmaceuticals (antibiotics, anti-inflammatories, barbiturates), caffeine and the nicotine metabolite cotinine.…”
Section: Point Source Termsmentioning
confidence: 80%
“…Halogenated hydrocarbons (perflurochemicals and polychlorinated alkanes) can be important groundwater contaminants due to their relatively high concentrations in sludge and high solubility [97]. Veterinary antibiotics, antimicrobials and saccharin have all been reported from soil manure applications [98][99][100].…”
Section: Diffuse Source Termsmentioning
confidence: 99%